SUSTAINABLE STRATEGY FOR DANANTARA: POSITIONING INDONESIA’S SOVEREIGN WEALTH FUND FOR GLOBAL COMPETITIVENESS AND RESPONSIBILITY - Rossa Esyam (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study aims to formulate a sustainable strategy for Danantara, Indonesia’s newly launched sovereign wealth fund (SWF), to become a globally competitive and responsible investment entity. It investigates how Triple Bottom Line (TBL) can guide Danantara in achieving long-term economic, social, and environmental goals. This research uses qualitative descriptive analysis supported by strategic frameworks such as PESTEL, VRIO, CPM, SWOT, and QSPM. The data was synthesized from policy documents, strategic reports, and literature on SWF best practices (e.g., Temasek, Khazanah). TBL and ESG principles were applied to evaluate Danantara’s investment posture. The analysis reveals that Danantara’s large initial capital and political support provide strategic strength, yet internal inexperience and governance risks pose challenges. Strategy B (phased consolidation with internal strengthening and partnerships) is identified as the most sustainable path forward. This strategy aligns with Triple Bottom Line (TBL) principles by promoting inclusive governance that supports social well-being (People), ensuring investment prudence and financial sustainability (Profit), and maintaining a strong commitment to environmental responsibility (Planet).